Studies on biological activity of synthetic mannich base nitrogen mustard of 3 – aminophthalimide – 1 - Kumar, Jainendra; Sinha, Girish Kumar; Kumar, Manindra; Sheel, Rimjhim (International Multidisciplinary Research Journal, 2012)
Synthetically prepared N - bis (2 - Chloroethyl) amino – methylene - 3 - aminophthalimide (m.p. 84o) showed definite fungicidal effect on Aspergillus species at 5% or higher concentration of the compound in ethyl alcohol. Lower doses did not show any degree of lethality when pure culture of Aspergillus flavns was treated by filter paper discs of the test solutions. The compound may further be tested for its fungicidal property in vivo for its promotion as a possible anti-fungal drug and a compound active against aspergilloses.